RE-APPRAISING THE ROLE OF PHILOSOPHICAL BASES FOR TEACHING ENGLISH REFLECTED IN THE CURRENT CURRICULUM IN INDONESIA - Widhiyanto, - (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2011)
This article discusses the philosophical bases of the current curriculumÃ¢â¬âSchool-Based Curriculum, which is considered as the simplified version of the previousÃ¢â¬âCompetency Based Curriculum. The aim of this discussion is primary to re-visit the theories that teacher may have overlooked. It also deals with possible application of the theories in the real teaching and learning of English. Hopefully, this may contribute to the understanding of the current curriculum better. ÃÂ Keywords: curriculum, communicative competence, systemic functional linguistics, ZPD, literacy education